Pathogenic Bacterial Nasopharyngeal Colonization and Its Impact on Respiratory Diseases in the First Year of Life: The PATCH Birth Cohort Study. Issue 6 (June 2015) - Tsai, Ming-Han; Huang, Shu-Huan; Chen, Chyi-Liang; Chiu, Chih-Yung; Hua, Man-Chin; Liao, Sui-Ling; Yao, Tsung-Chieh; Lai, Shen-Hao; Yeh, Kuo-Wei; Wang, Mei-Ping; Huang, Jing-Long
Abstract : Background: For acute respiratory diseases caused by bacteria, colonization in the respiratory tracts is often the first sign, although nasopharynx is the major source of secretions containing pathogens. To understand the pathogenesis of respiratory tract diseases, it is important to analyze the establishment of nasopharyngeal bacterial colonization. Methods: Infants with nasopharyngeal swabs were examined at the age of 1, 2, 4, 6 and 12 months for the detection of pathogens, including Streptococcus pneumoniae, Hemophilus influenzae, Moraxella catarrhalis, Streptococcus pyogenes and Staphylococcus aureus. The methods used for detection were bacterial culture and multiplex polymerase chain reaction. Results: From January 2012 to August 2013, a total of 320 neonates were enrolled, and 120 of them completed the first 12-month study. Staphylococcus aureus was the most common pathogen at all 5 time points while the rates declined; in contrast, the other 4 increased during the first year of life. Of our series, the multiplex polymerase chain reaction detection rates were higher than those of bacterial culture. More than 50% of Staphylococcus aureus was methicillin-resistant, and the trend decreased in the same period. In the analysis of factors associated with the development of infant wheeze, infants with maternal atopy [odds ratio (OR): 3.26; 95% confidence interval (CI): 1.20–8.88; P = 0.02] and pneumococcal colonization (OR: 15.64; 95% CI: 3.25–75.35; P = 0.001) had higher rates of wheeze. Conclusions: Bacterial interactions may result in differing pathogen prevalence in the first year of life. In addition, nasopharyngeal pneumococcal colonization may have an effect on the risk of infant wheeze. The result could help clinicians to clarify the relation between bacterial colonization and respiratory illnesses in infancy.